Food and Nutrition Education as a health promotion strategy in School Feeding Programs in South America (Research, Society and Development, 2025)
This study aims to analyze the presence and strategies of Food and Nutrition Education (FNE) in school feeding programs in South American countries, considering four main approaches: the existence of FNE strategies, the inclusion of the topic in the school curriculum, the definition of the target audience, and the participation of nutritionists in the program. The research was conducted through document analysis, using official national documents and legislation, and international reports. It was found that, although most countries have legal frameworks related to FNE, there are differences in how the topic is structured and implemented. Despite the limitations regarding the consolidation of FNE as a continuous and integrated practice, the study reinforces its relevance as a strategy in addressing childhood obesity and promoting healthy eating habits in the school environment. The normative advances indicate progress, but further efforts are still needed to strengthen the implementation, monitoring, and evaluation of FNE actions in South American countries.